EXPERIMENTAL WOUND HEALING ASPECTS OF JASMINUM GRANDIFLORUM LINN: A PRECLINICAL STUDY - Mittal, Arun; Satish, Sardana; Anima, Pandey (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Jasminum grandiflorum is an important shrub of family Oleaceae and ancient literature mentions its various medicinal uses especially its efficacy in wound healing. To substantiate its traditional claim the present study was conceived. Materials and Methods: Preliminary wound healing activity of successive extracts of leaves was assessed by measuring wound contraction using excision wound model and the detailed study of most potent extract was evaluated by measuring wound contraction, epithelialization period, hydroxyproline content, tissue breaking strength and histopathology parameters by excision and incision wound models. The antioxidant activity was determined by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method. The agar well-diffusion method and minimum inhibitory concentration (MIC) was used to established antimicrobial efficacy. Results: The results show that successive ethanolic extract of the leaves exhibited promising wound healing, antioxidant and antimicrobial properties. Conclusion: From results; it is concluded that its traditional use for the treatment of wound and in microbial infection is justified.